Cholelithiasis, choledocholithiasis and hepatolithiasis with secondary necrotizing hepatitis and cholangiohepatitis in a dairy cow - Guedes, Amanda R.; Gonçalves, Eldo; Paulino, Ruan; Andrade Neto, Adony Querubino de; Souto, Rodolfo José Cavalcanti; Afonso, José Augusto B.; Arenales, Alexandre (Brazilian Journal of Veterinary Pathology, 2021)
Biliary calculi are rare in cattle and occur usually in the gallbladder without clinical signs. In humans, colelithis are a common cause of hepatic abscessation due calculi microbiota. Here is described a case of cholelithiasis, coledocolithiasis and hepatolithiasis in a 10-year-old female mixed breed dairy cow. The animal died during physical examination with signs as cachexia, icterus and fever. At necropsy, a large number of green calculi were observed in the gallbladder, common duct lumen and in markedly distended biliary ducts. The liver was firm and decreased in volume with multiple abscess and multiple red foci measuring 0.5 cm in diameter in the hepatic parenchyma. Microscopically in the liver, marked ductal proliferation and abscedative cholangiohepatitis with abundant fibrosis and multiple foci of hepatocytes necrosis. In conclusion coledocolithiasis and hepatolithiasis may occur in cattle and cause significant clinical signs and pathological alterations.